Parental stress among patients with schizophrenia spectrum disorder in Hospital Kuala Lumpur / Fatimah Emran - Emran, Fatimah (2019)
Background: Parental stress among patients with schizophrenia spectrum disorder is detrimental and often associated with adverse outcome. This vulnerable group of people often struggles with their psychiatric symptoms and adverse effects of medication which may interfere with optimal parenting. Being disadvantaged, they reported multiple challenges in parenting their children, which may all contribute to parental stress. Hence, identifying factors contributing to parental stress is crucial so that adequate support and holistic treatment can be delivered to the patients, in order to ensure well-being of both parents and children. Objective: To determine the prevalence of parental stress among patients with schizophrenia spectrum disorder, to identify the associated factors contributing to parental stress, and the association between severity of psychiatric symptoms with parental stress. Methodology: This is a cross-sectional study involving 115 patients with schizophrenia spectrum disorder who were attending psychiatric clinic in Hospital Kuala Lumpur, recruited through universal sampling. Those who fulfilled the selection criteria and gave informed consent were selected. Socio-demographic data, perceived parenting capacity, children data, and illness data were obtained from the patient during interview as well as from the clinical notes. Presence of parental stress and severity of psychiatric symptoms were measured using Parental Stress Scale (PSS) and Brief Psychiatric Rating Scale (BPRS) respectively. Descriptive analysis was performed, followed by univariate analysis and multiple logistic regression analysis. Results: Of the total 115 participants, 60 (52.2%) patients with schizophrenia spectrum disorder had parental stress. The presence of parental stress was significantly associated with being non-Malay (χ² (1, n =115) = 4.610, p =0.032), lower household income or among Bottom 40 group (χ² (1, n =115) = 3.241, p =0.004), parenting children with mental or learning disability (χ² (1, n =115) = 5.213, p =0.022), and symptomatic of psychiatric symptoms (χ² (1, n =115) = 11.640, p =0.001). There was significant association between severity of psychiatric symptoms and parental stress (p =0.004). Conclusion: Parental stress is prevalent among patients with schizophrenia spectrum disorder. Being non-Malay, lower household income, parenting children with mental or learning disability, and symptomatic of psychiatric symptoms contribute to parental stress among this vulnerable population. Hence, health care professional should actively recognize any warning signs and provide them with necessary supports to reduce serious implications associated to parental stress.